Constitutional justice as a principle of the rule of law - Ongdashuly, Y.; Baikenzheyev, A.S.; Toksanova, M.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The purpose of the article is to understand constitutional justice as necessary conditions and security forming principles in the Republic of Kazakhstan of the legal space, ensuring its rule of law and democratization of public relations through the mechanism of control over compliance with the provisions of the Constitution, which has proven its effectiveness in the world practice of the development of the constitutional process. The article examines the problems associated with understanding the substantive foundations of the principles of the rule of law; an analysis of the state of the process of using principles in the activities of the Constitutional Court of the Republic of Kazakhstan is carried out. Research methods. The author relied on the methodology of constitutional and legal science, which is based on the principle of differential knowledge of constitutional processes in their relationship with the institutional support of constitutionalism in the process of working on the article. A method of cognition also used a systemic, logical method, as well as a method of systemic-structural analysis of normative legal acts, to disclose the problems raised in the article. Research results. The rights of supremacy are a complex implementation of realities, a system of additional elements, in which the absence of at least one of them makes the functioning of the system impossible. Carrying out constitutional justice, the Constitutional Court of the Republic of Kazakhstan contributes to the preservation of constitutional legality, and the presence of constitutional justice should be considered one of the main directions of ensuring the supremacy in the country. Conclusions. The mandatory implementation of constitutional justice in the Republic of Kazakhstan should be considered as the main principle of ensuring the supremacy of rights, taking office, in accordance with the fundamental significance of the Basic Law, consisting in its ability to ensure the development and functioning of national legislation based on constitutions, when this "compliance" itself is required in the Republic of Kazakhstan in the control by the constitutional justice bodies.